New medicines for childhood-onset systemic lupus erythematosus: an EU perspective on paediatric drug development - De Lisa, Roberto; de Andres-Trelles, Fernando; Bax, Ralph; Galluzzo, Sara; Alward, Brian; Thomson, Andrew; Karres, Dominik; Brunner, Hermine I.; Ruperto, Nicolino; Egger, Gunter F. (Frontiers in Medicine, 2025)
Childhood-onset systemic lupus erythematosus (cSLE, also known as juvenile or paediatric SLE) is a severe autoimmune disease affecting multiple organs and systems, with higher morbidity and severity compared to adult SLE (aSLE). The European Union’s Paediatric Regulation No. 1901/2006 mandates the agreement of a paediatric investigation plan (PIP) for new investigational medicinal products (IMPs) to ensure reliable efficacy and safety data for paediatric indications. This study examined the experience of the Paediatric Committee (PDCO) at the European Medicines Agency (EMA) in assessing PIPs for cSLE, highlighting the challenges and potential solutions in the planning of development of novel agents in this disease and providing the academia point of view on key points of cSLE medicines development. Regulatory requirements so far have been rather consistent when a PIP is agreed, and recommend randomised controlled trials to enable a full benefit-risk assessment. However, PIPs are agreed when adult efficacy data are not yet available and as soon as the product lifecycle progresses, new methods and approaches can offer some advantages over randomised controlled trials in this setting and might provide a comparable level of evidence of efficacy in an alternative way. Extrapolation of adult efficacy data to paediatrics is one possible approach, provided that adult trials produce data that can be used for this purpose and that the degree of residual uncertainty is appropriately quantified for the medicinal product in question. The study also highlights the value of enhanced international cooperation among regulatory authorities, developers, and academic institutions in this field to support collaborative efforts among various stakeholders.